ANALISIS BIAYA PRODUKSI AMPLANG IKAN BANDENG PADA PT AHAR SENTOSA BKI MAMUJU - Nur Aida; Feronica Pungky Muchsidin; Nuraeni Saeni; A. We Tenri Fatimah S; Pretty Margarethe Apriliani P (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Milkfish is one of the export commodities known as milkfish. Amplang ikan bandeng or in Sulawesi is called sponge fish, which is a snack type of cracker with a distinctive taste and aroma of fish. PT Ahar Sentosa bki is an individual PT which was established in 2012 which is one of the businesses that produce Amplang. At PT Ahar sentosa bki, there is a decrease in turnover in certain months, especially in January due to the influence of weather. The phenomenon that occurs in this company is that the calculation has not used the method of calculating the cost of goods produced correctly, only calculating in a simple or traditional way, not detailing all costs incurred. The purpose of this study is to analyze the production cost of milkfish Amplang using the full costing method at PT Ahar Sentosa Bki Mamuju. The analysis method used is quantitative descriptive using a report on the production cost of milkfish amplang. The data used was obtained from PT Ahar Sentosa Bki Mamuju The analysis of production costs uses the full costing method to produce the cost of goods produced. Based on the results of the analysis, it shows that the cost of production of milkfish amplang at PT Ahar Sentosa using the full costing method is Rp.505,193,766 and according to the company Rp. 493,684,600 has a difference of Rp. 11,509,166. and the difference in the cost of goods produced by packs Rp.128.